Searching for a Signal: Self-Reported Kratom Dose-Effect Relationships Among a Sample of US Adults With Regular Kratom Use Histories - Smith, Kirsten E.; Rogers, Jeffrey M.; Dunn, Kelly E.; Grundmann, Oliver; McCurdy, Christopher R.; Schriefer, Destiny; Epstein, David H. (Frontiers in Pharmacology, 2022)
There is limited understanding regarding kratom use among US adults. Although motivations for use are increasingly understood, typical kratom doses, threshold of (low and high) doses for perceived effectiveness, and effects produced during cessation are not well documented. We aimed to extend prior survey work by recruiting adults with current and past kratom exposure. Our goal was to better understand kratom dosing, changes in routines, and perception of effects, including time to onset, duration, and variability of beneficial and adverse outcomes from use and cessation. Among respondents who reported experiencing acute kratom effects, we also sought to determine if effects were perceived as helpful or unhelpful in meeting daily obligations. Finally, we attempted to detect any signal of a relationship between the amount of kratom consumed weekly and weeks of regular use with ratings of beneficial effects from use and ratings of adverse effects from cessation. We conducted an online survey between April-May 2021 by re-recruiting participants from a separate study who reported lifetime kratom use. A total of 129 evaluable surveys were collected. Most (59.7%) had used kratom >100 times and reported currently or having previously used kratom >4 times per week (62 weeks on average). Under half (41.9%) reported that they considered themselves to be a current “regular kratom user”. A majority (79.8%) reported experiencing acute effects from their typical kratom dose and that onset of effects began in minutes but dissipated within hours. Over a quarter reported that they had increased their kratom dose since use initiation, whereas 18.6% had decreased. Greater severity of unwanted effects from >1 day of kratom cessation was predicted by more weeks of regular kratom use (β=6.74, p=0.02). Acute kratom effects were largely reported as compatible with, and sometimes helpful in, meeting daily obligations. In the absence of human laboratory studies, survey methods must be refined to more precisely assess dose-effect relationships. These can help inform the development of controlled observational and experimental studies needed to advance the public health understanding of kratom product use.